AKTIVITAS ANTIOKSIDAN DAUN KESEMEK (Diospyros kaki L.F) DENGAN METODE DPPH (2,2-DIFENIL-1 PIKRILHIDRAZIN) - Isnindar Isnindar; Erna Prawita Setyowati; Subagus Wahyuono (Majalah Obat Tradisional, 2011)
There are two groups of antioxidant resources, these are synthetic and natural antioxidants. The most important natural antioxidant is phenolic compounds that are produced naturally from plants. Phenolic Antioxidants are potent antiradical, biologically active as they are able to donate hydrogens to free radicals and break the chain of lipid oxidation reactions in the early stages. This study is aimed to search natural antioxidant compounds from the leaves persimmon (Diospyros kaki L.F) that have been utilized traditionally to prevent from sickness. In order to detect the presence of antioxidant compounds in the leaves extract, a reagent of DPPH (2,2-diphenyl-1-pykrilhidrazine) in methanol was used. Initially, powder of persimmon leaves (115 g) is macerated 3 times with methanol, 24 hours each time at room temperature. The liquid extract obtained is evaporated by rotavapor till residue (methanol extract) (phase I) is obtained. The residue was then extracted with CHCl3 to give CHCl3 soluble (phase II) and insoluble fractions. The later is then extracted with water to give water soluble (phase III) and insoluble fractions. These fractions (phase I-III) are chromatophed by TLC and sprayed by DPPH. Phase II contains antiradical compounds as shown by yellow color on the violet background. By preparative TLC [SiO2, CHCl3-EtOAc (1-4 v/v)], antiradical substance is isolated and identified tentatively as substituted phenolic compounds. Antiradical potential is measured spectrophotometrically, the isolat shows IC50 at 107.7 μg/mL that is lower than that of vitamin C (3.04 μg/mL).